Analisis Teori Penerapan Panel Surya pada Lampu Jalan Tol - Adi Sutopo; Muhammad Dani Sohilin; Kimi Bonari Siahaan; Muhammad Syauqi Adnan; Christiano Togatororp; Michael Cristy; Azmi Nasution (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
In today’s era, the use of renewable energy is increasingly becoming a major focus in energy increasingly becoming carbon emissions. One of the applications of renewable energy in industrial life is the use of solar panels for street lighting systems, especially on toll road lights that require continuous and efficient lighting. This study aims to analyze the basic theory of how solar panels work an their application to toll road lights, taking into account energy efficiency, power deviation, and stability of electricity supply. The analysis method is carried out through literature studies and mathematical calculation in the application of solar panels to toll road lights. The result of the analysis show that the solar panle system is able to meet the energy needs of toll road lights, especially in areas with high sunlight intensity. In addition, the use if lithium batteries as energy storage has proven effective in maintaining the stability of electricity supply at night or in cloudy weather